Tháng Năm 29, 2022

Gọi \({x_0}\) là số thỏa mãn \(x.\left( {2018 + \frac{1}{{2018}} – 2019 – \frac{1}{{2019}}} \right) = \frac{1}{3} + \frac{1}{6} – \frac{1}{2}.\) Khi đó:

Gọi \({x_0}\) là số thỏa mãn \(x.\left( {2018 + \frac{1}{{2018}} – 2019 – \frac{1}{{2019}}} \right) = \frac{1}{3} + \frac{1}{6} – \frac{1}{2}.\) Khi đó:

A. \({x_0} > 0\)

B. \({x_0} < 0\)

C. \({x_0} = 0\)

D. \({x_0} = 1\)

Hướng dẫn

Chọn đáp án là: C

Phương pháp giải:

Tính giá trị bên vế phải rồi đưa về dạng tìm \(x\) đã học.

\(\begin{array}{l}x.\left( {2018 + \frac{1}{{2018}} – 2019 – \frac{1}{{2019}}} \right) = \frac{1}{3} + \frac{1}{6} – \frac{1}{2}\\x.\left( {2018 + \frac{1}{{2018}} – 2019 – \frac{1}{{2019}}} \right) = 0.\end{array}\)

Mà \(2018 + \frac{1}{{2018}} – 2019 – \frac{1}{{2019}} = – 1 + \frac{1}{{2018}} – \frac{1}{{2019}} < 0\) nên \(x = 0\) .

Chọn C.